Health promotion with mental health workers - Bitencourt Toscani Greco, Patrícia (2019)
Objective: To report the experience of undergraduate students in the development of health promotion actions with mental health workers. Data Synthesis: This experience report was developed by nursing students from a university in Rio Grande do Sul, Brazil, to address the development of health promotion actions with mental health workers. A total of eight meetings were held from 2015 to 2016 and the themes addressed were aimed at the reflection and discussion about the work process, professionals’ quality of life, and performance of activities to promote occupational health using spaces for reflection and activities to promote health and prevent diseases. Conclusion: The activities held by undergraduate students with the population of mental health workers favored a differentiated look at the aspects that involve occupational health and allowed the development of interdisciplinary teamwork among undergraduate courses.